Clothing industry: development problems, regional dislocation and modern management technologies for small enterprises - I. Hristoforova; T. Arkhipova; A. Demenkova (Модернизация, инновация, развитие, 2016)
This article discusses issues related to the problems of development of light industry in the territory of the former Soviet Union, systematize industry regions and analyzes modern management technologies used by small businesses garment industry. The aim of the article is the analysis of the organizational and economic aspects of light industry on the example of clothing companies. The objectives of the article: to sistematize the major regions of the dislocation of light industry: textile, footwear, clothing; to characterize the current state of the apparel industry enterprises; to show the value of small clothing companies; to study the need for the introduction of flexible manufacturing systems (FMS) on small sewing factories; to analyze the range of the scientific development of national universities in the study of flexible manufacturing systems and give them a brief description.Methodology. The methodological basis of the paper is the following scientific methods: deduction, comparative and group analysis, desk research. The Results. The result of the study is to identify the main issues and trends in the development of light industry, ordering the placement of the industry in the territory of the former Soviet Union, the definition of the most popular management techniques used in small businesses garment industry.Conclusions / significance. The above article analyzes the development of light industry has allowed to identify the main trends and formulate problems for the enterprises. New conditions require the development of small enterprises and the introduction of modern technologies in production processes and management.